An Amino Acid‐Based Thixotropic Hydrogel: Tuning of Gel Recovery Time by Mechanical Shaking. Issue 5 (1st February 2023) - Bassan, Ruchika; Varshney, Mayank; Roy, Subhasish
Abstract: Fmoc‐Trp‐OH (Fmoc: N‐fluorenylmethoxycarbonyl; Trp‐OH: L‐Tryptophan) undergone hydrogelation at 50 mM phosphate buffer saline of pH 7.4 with a minimum gelation concentration (MGC) of 0.25 % w/v after 12 to 15 hours. However, the hydrogel formation kinetics can be faster just by mechanical hand shaking of the hydrogelator solution during the hydrogel preparation procedure. The shake hydrogel is thermally and mechanically more stable than the non‐shake hydrogel. These hydrogels have been characterized thoroughly by T gel estimations, UV‐Vis spectroscopy, Fluorescence spectroscopy, Fourier Transform‐Infra Red (FT‐IR) Spectroscopy, X‐ray diffractions (XRD), Field Emission Scanning Electron Microscopy (FE‐SEM) and rheology. This amino acid‐based hydrogel is thixotropic in nature and interestingly without doping any foreign materials into the hydrogel, the gel reformation kinetics can be faster just by number of times breaking of the hydrogel by mechanical hand shaking followed by keeping the hydrogel glass vial at rest. This holds future promise to develop supramolecular mechanocatalyst for various functional group transformation reactions in water through green and sustainable chemistry pathways. Abstract : Fmoc‐Trp‐OH forms hydrogel after 12 to 15 hours at 50 mM phosphate buffer saline at pH 7.4 with a MGC of 0.25 % w/v. However, the hydrogel formation can be faster just by mechanical hand shaking during the hydrogel preparation procedure. Interestingly, the hydrogel is thixotropic in nature and the shake gel reformation kinetics, thermal and mechanical behavior can be tuned just by mechanical hand shaking and more interestingly without doping any foreign materials.